Lack of effective communication between communities and hospitals in Uganda: a qualitative exploration of missing links - Mutebi Aloysius; Walker Damien; Okui Olico; Ekirapa-Kiracho Elizabeth; Rutebemberwa Elizeus; Pariyo George (BMC, 2009)
Abstract Background Community members are stakeholders in hospitals and have a right to participate in the improvement of quality of services rendered to them. Their views are important because they reflect the perspectives of the general public. This study explored how communities that live around hospitals pass on their views to and receive feedback from the hospitals' management and administration. Methods The study was conducted in eight hospitals and the communities around them. Four of the hospitals were from three districts from eastern Uganda and another four from two districts from western Uganda. Eight key informant interviews (KIIs) were conducted with medical superintendents of the hospitals. A member from each of three hospital management boards was also interviewed. Eight focus group discussions (FGDs) were conducted with health workers from the hospitals. Another eight FGDs (four with men and four with women) were conducted with communities within a five km radius around the hospitals. Four of the FGDs (two with men and two with women) were done in western Uganda and the other four in eastern Uganda. The focus of the KIIs and FGDs was exploring how hospitals communicated with the communities around them. Analysis was by manifest content analysis. Results Whereas health unit management committees were supposed to have community representatives, the representatives never received views from the community nor gave them any feed back from the hospitals. Messages through the mass media like radio were seen to be non specific for action. Views sent through suggestion boxes were seen as individual needs rather than community concerns. Some community members perceived they would be harassed if they complained and had reached a state of resignation preferring instead to endure the problems quietly. Conclusion There is still lack of effective communication between the communities and the hospitals that serve them in Uganda. This deprives the communities of the right to participate in the improvement of the services they receive, to assume their position as stakeholders. Various avenues could be instituted including using associations in communities, rapid appraisal methods and community meetings.